Sadvertising and Sentiment: A Lexicon-Based YouTube Comment Analysis of Emotionally Resonant Thai Insurance Advertising - Andi Azhar; Arief Dwi Saputra; Alfina Rahmatia (Tecno Scientifica Publishing, 2026)
Sadvertising referred to the deliberate use of melancholic and empathetic narratives as a primary persuasive strategy in marketing communication. Although the genre had become commercially prominent, large-scale empirical evidence on how global audiences received such advertisements was still limited, and most prior sentiment studies had focused on product reviews or English-language Western markets rather than emotionally driven Southeast Asian advertising. This study examined whether emotionally resonant, narrative-driven advertising in the sadvertising genre produced predominantly positive sentiment among global digital audiences. A domain-adapted, rule-based lexicon sentiment analysis framework was applied to 2,498 YouTube comments scraped from a landmark Thai Life Insurance advertisement to quantify sentiment polarity, eight emotional response typologies, and engagement metrics across an 11-year observation window. The lexicon was constructed from established resources (VADER and the NRC Emotion Lexicon), extended with 30 emoji tokens and 47 negative terms specific to emotional advertising commentary, and validated against a 300-comment human-coded reference set with substantial inter-rater agreement (Cohen’s kappa = 0.79). Positive comments constituted 38.9% of the corpus (95% CI: 37.0–40.8%) compared to 6.4% negative comments (95% CI: 5.5–7.5%), yielding a positive-to-negative ratio of 6.04:1 (95% CI: 5.11–7.13). A chi-square goodness-of-fit test rejected the equal-proportions null hypothesis at p < 0.001 with a large effect size (Cohen’s w = 0.60). Crucially, 95.3% of crying-expression comments carried positive valence (95% CI: 92.8–97.0%), with a Cramer’s V of 0.51 and an odds ratio of 51.8 (95% CI: 32.36–82.91), empirically resolving the sad–positive paradox. Positive sentiment persisted across 11 years of engagement with no detectable temporal decay, and cross-cultural consistency was observed across at least 27 linguistic communities. The findings advanced sadvertising theory and carried direct implications for brand communication strategy in the digital era.